Plasma lipid levels in 10-to 13-year old Costa Rican elementary schoolchildren - Monge Rojas, Rafael (2000)
An adverse lipid profile is a major risk factor for atherosclerosis. This study evaluated the lipid profiles of 683 schoolchildren aged 10 to 13 years. The prevalence of both high LDL and high total cholesterol levels was significantly (p lower0,001) higher in private schoolchildren than in public schoolchildren. There were no significant differences in the prevalence of high triglyceride levels among the schoolchildren. Mean total cholesterol and LDL cholesterol levels were significantly higher in children whose parents had completed over 11 years of schooling. Private schoolchildren were more sedentary and tended to have a more atherogenic diet. Our data suggest that prevention programmes in primary schools are required to decrease the prevalence of cardiovascular risk factors, including abnormal lipid profiles.